Reversal of Delayed Vasospasm by TS-011 in the Dual Hemorrhage Dog Model of Subarachnoid Hemorrhage - Hacein-Bey, L.; Harder, D.R.; Meier, H.T.; Varelas, P.N.; Miyata, N.; Lauer, K.K.; Cusick, J.F.; Roman, R.J. (American Journal of Neuroradiology, 2006)
PURPOSE: Arachidonic acid is avidly metabolized to a potent vasoconstrictor, 20-hydroxyeicosatetraenoic acid (20-HETE), in the cerebral circulation. 20-HETE has been reported to contribute to the acute fall in cerebral blood flow following subarachnoid hemorrhage (SAH), but its role in the development of delayed vasospasm is unknown. The present study examined whether delayed vasospasm is associated with elevations in 20-HETE in CSF in the dual hemorrhage model of SAH in dogs and if blockade of the synthesis of 20-HETE with N-(3-chloro-4-morpholin-4-yl)phenyl-N’-hydroxyimido formamide (TS-011) can reverse delayed vasospasm in this model.MATERIALS AND METHODS: Delayed vasospasm was induced in 22 adult beagle dogs by dual injection of blood (0.5 mL/kg) into the cisterna magna on days 1 and 4. Sequential samples of CSF were collected before intracisternal injections of blood on days 1 and 4 and after the development of delayed vasospasm on day 7. Sequential angiograms were obtained before and after intracisternal injection of blood on days 1 and 4 and before and 1 hour after administration of TS-011 (1 mg/kg IV) on day 7.RESULTS: The dogs consistently developed delayed vasospasm, and the diameter of the basilar artery fell to 68 ± 3% (n = 15), 3 days after the second intracisternal injection of blood. The levels of 20-HETE in CSF increased from 4 ± 2 to 39 ± 16 pg/mL. In 9 dogs with delayed vasospasm, acute blockade of the synthesis of 20-HETE with TS011 (1 mg/kg IV) significantly increased the diameter of the basilar artery by 39%. Chronic administration of TS-011 (1 mg/kg per day) attenuated the development of delayed vasospasm, and the diameter of the basilar artery fell by 17 ± 1% versus the 33 ± 3% decrease in diameter seen in control animals 3 days following the second injection of blood into the cisterna magna.CONCLUSIONS: These results indicate that the development of delayed vasospasm in dogs is associated with an increase in 20-HETE levels in CSF, and acute blockade of the synthesis of 20-HETE with TS-011 reverses delayed vasospasm in this model.